2011
DOI: 10.1161/atvbaha.111.229070
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Regulates Vascular Gene Transcription via Oxidative Stress–Dependent and –Independent Pathways

Abstract: Objective Aldosterone (Aldo) antagonism prevents cardiovascular mortality by unclear mechanisms. Aldo binds to the mineralocorticoid receptor (MR), a ligand-activated transcription factor, which is expressed in human vascular cells. Here we define the early Aldo-regulated vascular transcriptome and investigate the mechanisms of gene regulation by Aldo in the vasculature that may contribute to vascular disease. Methods and Results Gene expression profiling of Aldo-treated mouse aortas identified 72 genes regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 44 publications
6
82
0
2
Order By: Relevance
“…29,30 We and others, have previously showed that Lcn2/NGAL is a direct target gene of the aldosterone/MR signaling pathway in the cardiovascular system. 5,31,32 The aim of this study was to analyze whether Lcn2/NGAL is a key actor of mineralocorticoid action in the cardiovascular system. We analyzed 2 conditions associated with increased aldosterone/MR activation (AO in human subjects and NAS challenge in a mouse model with Lcn2 gene deletion) and provide mechanistic insights in the profibrotic effects of Lcn2/NGAL.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 We and others, have previously showed that Lcn2/NGAL is a direct target gene of the aldosterone/MR signaling pathway in the cardiovascular system. 5,31,32 The aim of this study was to analyze whether Lcn2/NGAL is a key actor of mineralocorticoid action in the cardiovascular system. We analyzed 2 conditions associated with increased aldosterone/MR activation (AO in human subjects and NAS challenge in a mouse model with Lcn2 gene deletion) and provide mechanistic insights in the profibrotic effects of Lcn2/NGAL.…”
Section: Discussionmentioning
confidence: 99%
“…29 Our results suggest that this increase may be induced (at least partly) by aldosterone. It has been demonstrated that aldosterone regulates CTGF expression ex vivo in various cell types (fibroblasts, 20 smooth muscle cells, 30 and renal mesangial cells) 31 including cardiomyocytes. 32 However, we show here for the first time that CTGF is a direct target of MR, and that aldosterone (but not corticosterone) increases CTGF expression in cardiomyocytes through the stimulation of cardiomyocyte-MR in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mineralocorticoids can also induce CTGF through other pathways, in the heart, in a serum/glucocorticoid regulated kinase 1-dependent manner 20 and in the vasculature, in an oxidative stress-dependent manner. 30 This does not mean that these pathways are mutually exclusive, and convergent signaling may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Further candidate MR target genes are proposed through transcriptome analyses on renal, aortic and cardiac tissue after exposure to aldosterone. These have diverse functions in cell signal transduction, oxidative stress, inflammatory mediators, steroid biosynthesis, receptor chaperoning, cellular structure, adhesion and migration (Turchin et al 2006, Latouche et al 2010, Newfell et al 2011, Ueda et al 2014. Comparison between mice with cardiac overexpression of either GR or MR suggests that there is surprisingly little overlap in GR-and MR-regulated genes in the heart (Latouche et al 2010).…”
Section: Expression Of Mr Target Genesmentioning
confidence: 99%